2020
DOI: 10.18494/sam.2020.2927
|View full text |Cite
|
Sign up to set email alerts
|

Realization of 3D Aqua Hologram Augmented Reality of Robot Fish

Abstract: This paper is about the realization of robot fish motion along with 3D hologram fish in an aquarium, with the augmented reality of 3D aqua holograms to attract viewers. In this new proposed concept, the animated fish video with 3D hologram is projected into a robot fish aquarium. However, this process of projecting 3D hologram fish into a robot fish aquarium may cause the overlap of the robot fish with the animated fish. To avoid this problem of overlapping, sensors play an important role. Image sensors track … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The shortcomings of 3D hologram media of the solar system include, (1) the size of the media is less large, (2) the use of media must be supported by speakers so that planetary explanations can be heard more clearly, and (3) the process of making animated videos that take a long time. The lack of media is not a very crucial problem, because hologram 3D media also has many advantages, namely, (1) the process of making display pyramids that are easy to make, (2) materials to make media easy to find, (3) the use of media that is easy to simply place the display pyramid on a smartphone or laptop screen, (4) media is easy to carry anywhere, (5), the use of media attracts the attention of learners because it combines the real world with technology and (6) hologram 3D media is included in environmentally friendly media because the display pyramid can also be made from the head of a clear mineral water bottle. So it can be concluded that hologram 3D media is very effective in the post-pandemic learning process as a motivation and encouragement for students in fighting learning saturation.…”
Section: Icmscementioning
confidence: 99%
See 1 more Smart Citation
“…The shortcomings of 3D hologram media of the solar system include, (1) the size of the media is less large, (2) the use of media must be supported by speakers so that planetary explanations can be heard more clearly, and (3) the process of making animated videos that take a long time. The lack of media is not a very crucial problem, because hologram 3D media also has many advantages, namely, (1) the process of making display pyramids that are easy to make, (2) materials to make media easy to find, (3) the use of media that is easy to simply place the display pyramid on a smartphone or laptop screen, (4) media is easy to carry anywhere, (5), the use of media attracts the attention of learners because it combines the real world with technology and (6) hologram 3D media is included in environmentally friendly media because the display pyramid can also be made from the head of a clear mineral water bottle. So it can be concluded that hologram 3D media is very effective in the post-pandemic learning process as a motivation and encouragement for students in fighting learning saturation.…”
Section: Icmscementioning
confidence: 99%
“…Visual reality, augmented reality, and holograms are examples of technological developments that are being hotly discussed today. Many researchers developed 3D holograms and applied them in filmmaking, information technology, and other communication sectors [5]. Curriculum 2013 (K-13) is one of the curricula that demands the learning process by utilizing information technology and visual communication [6].…”
Section: Introductionmentioning
confidence: 99%
“…(4), u and v are respectively the horizontal and vertical directions of the optical flow, which are also known as motion vectors. (14)(15)(16)(17) To compute the motion vectors, the optical flow limitation equation [Eq. (5)] is used with the Lucas-Kanade method.…”
Section: Optical Flow Algorithmmentioning
confidence: 99%